2021
DOI: 10.2478/forj-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of maturity age for coppice oak forests within Left-Bank Forest-Steppe in Ukraine

Abstract: Oak (Quercus robur L.) forest stands are among the most common forest formations in the forest-steppe zone of Ukraine. Investigations of the patterns of distribution of trees by diameter and the dynamics of the commodity structure of mature oak stands of coppice origin were carried out based on the forest survey data from 28 temporary sample plots, on the sites designated for the final felling in the Left-Bank Forest Steppe of Ukraine (Sumy, Kharkiv, and Poltava Regions). We distributed trees by diameter class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Test plots were planted in conditions of moist poor pine site (A2) and relatively poor pine site (B2) in plantations of different ages. The terminology of the typology of forest vegetation sites is given in the publication [18]. Field and laboratory methods.…”
Section: Methodsmentioning
confidence: 99%
“…Test plots were planted in conditions of moist poor pine site (A2) and relatively poor pine site (B2) in plantations of different ages. The terminology of the typology of forest vegetation sites is given in the publication [18]. Field and laboratory methods.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the harvest age of oaks varies considerably from region to region due to differences in species, growing conditions, and commercial purposes, but generally ranges from 70 to 160 years and is concentrated in most regions between 80 and 100 years, as oak growth and timber quality are at a high level during this harvest period [68][69][70][71]. Tkach et al argued that the harvest age of oaks must consider forest senescence beyond 120 years because the health of oak forests with production times of 131-140 years is deteriorating in Ukraine [72]. However, our study showed that in the medium-quality STG2 and STG3, the production time of oaks with 60 cm target diameters is over 200 years, at which time the risk of tip breakage, timber heart rot, and reduced growth will increase significantly, resulting in the reduction in the commercial value of the timber.…”
Section: Harvest Age Of Different Target Diametersmentioning
confidence: 99%
“…For example, the growth and differentiation of the structure and composition of species are dominant processes in the case of former coppices, where variations in biomass distribution, population dynamics, regeneration, intra-and inter-specific selection, and ecological functions lead to significant changes in both abiotic and biotic conditions. [30,[48][49][50][51][52][53][54]. Given the importance of synecological and environmental factors, including climate change and variability, the characterization of the main phenotypes is another important step to achieve an understanding of the processes in place in relation to the characteristics of the site, environmental variability, previous silvicultural management and changes in the trends of climatic variables.…”
Section: The Analytical Planning Schemementioning
confidence: 99%